Laparoscopic treatment of pyogenic liver abscess complicating Crohn’s disease: A case report* - Bilgi BACA; İsmail HAMZAOĞLU and Tayfun KARAHASANOĞLU and Hülya Över HAMZAOĞLU (Turkish Journal of Gastroenterology, 2019)
-